Heritage, public history and democracy - Ničić Miloš; Iguman-Glušac Sanja (Filozofija i Društvo, 2025)
This paper examines the complex relationship between heritage, public history and democracy, arguing that heritage is not a neutral transmission of the past but a contested, constructed and politically charged process. Drawing on critical heritage studies and public history scholarship, the text evaluates how dynamic memory practices can both empower communities and reinforce existing power structures. Special attention is paid to the concept of dissonant heritage, which challenges singular narratives by exposing the omissions, silences and exclusions inherent in heritage-making processes. In contexts where democratic institutions are fragile or delegitimised, the paper identifies grassroots, bottom-up heritage initiatives as spaces for civic interventions and resistance. This work advocates participatory and reflective heritage practices, positioning heritage and public history as essential tools for democratic engagement and future-oriented cultural governance.